Boron isotope tracers of diffusion during glass dissolution - Thomas L.* Goût1; Guo, Rui; Sambuddha Misra; dward T. Tipper; Madeleine S. Bohlin; Yandi Hu; Ian Farnan (Environmental and Biogeochemical Processes, 2025)
The dissolution of waste glasses by groundwater presents a key mechanism for immobilised or encapsulated contaminant release over geological timescales. Accurately predicting glass dissolution rates remains a challenge to waste management, where a complete understanding of glass dissolution mechanisms is required to model the release and fate of contaminants. Here, this work investigated the suitability of boron isotope fingerprinting techniques for studying glass dissolution mechanisms, focussing on solid-state diffusion processes during boron release. Two glasses (magnesium-free 10B-ISG and magnesium-bearing 6Li-Mg-EM) were altered in deionised water at 90 °C for 0.25 to 112 d. Solution renewal experiments were used to further study altered surface layer properties. At ≤ 28 d, solution boron isotope (11B/10B) ratios for 6Li-Mg-EM were consistent with the apparent congruent release of boron alongside sorption/coprecipitation processes with secondary minerals, but decreasing solution 11B/10B ratios at > 28 d suggested diffusion occurred across the altered layer at a dissolution front spatially separated from that of lithium. Contrastingly, solution 11B/10B ratios for 10B-ISG at ≤ 28 d were fitted well using a diffusion model assuming a time-dependent apparent diffusion coefficient, but those at > 28 d were better explained by either sorption/coprecipitation processes with secondary minerals or a spatially-dependent apparent diffusion coefficient. The altered layer formed for 10B-ISG after 28 d was not protective following solution renewal, and renewed solution 11B/10B ratios were instead consistent with an apparent congruent release mechanism. This study presents boron isotopes as in situ tracers for studying glass dissolution mechanisms, assisting in predicting contaminant releases during waste glass-aqueous solution interactions.